1989
DOI: 10.1159/000181271
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Pituitary Volume in Children with Short Stature: Clinical and Radiological Correlates

Abstract: A retrospective evaluation of 80 cases of growth retardation evaluated at the Hôpital Sainte-Justine of Montreal has revealed that 20 of them (25 %; 15 boys and 5 girls) had a reduction of pituitary volume as revealed by high-resolution CT scanning of the pituitary gland. Of these patients, 8 had complete growth hormone (GH) deficiency, as evaluated by arginine infusion and L-Dopa-propranolol testing and nocturnal blood sampling, and 3 had GH neurosecretory dysfunction. Five patients had combined or multiple h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…(J Clin Endocrinol Metab 73: [79][80][81][82][83]1991) I DIOPATHIC hypopituitarism is a heterogeneous group of disorders of unknown etiology (1). Perinatal and postnatal complications are reported to be responsible for reduced sellar and pituitary volumes by computed tomography scan in large numbers of hypopituitaric patients (2)(3)(4)(5). Magnetic resonance (MR) imaging offers the advantage of revealing hypothalamic-pituitary abnormalities, such as pituitary hypoplasia, absence of the stalk and posterior lobe ectopia in many GH-deficient (GHD) patients (6)(7)(8)(9)(10)(11)(12); the underlying cause of these anatomic defects could be developmental in origin, dating from early intrauterine life (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(J Clin Endocrinol Metab 73: [79][80][81][82][83]1991) I DIOPATHIC hypopituitarism is a heterogeneous group of disorders of unknown etiology (1). Perinatal and postnatal complications are reported to be responsible for reduced sellar and pituitary volumes by computed tomography scan in large numbers of hypopituitaric patients (2)(3)(4)(5). Magnetic resonance (MR) imaging offers the advantage of revealing hypothalamic-pituitary abnormalities, such as pituitary hypoplasia, absence of the stalk and posterior lobe ectopia in many GH-deficient (GHD) patients (6)(7)(8)(9)(10)(11)(12); the underlying cause of these anatomic defects could be developmental in origin, dating from early intrauterine life (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Whereas relationship of hypopituitarism to reduced sellar and pituitary size shown by computed tomography has already been documented (2)(3)(4)(5), little is known about endocrinological findings in GHD patients investigated by MR imaging. Kikuchi et al (7) have suggested that the magnitude of hormone responses to stimuli in GHD children with hypothalamic-pituitary abnormalities evidenced by MR imaging is unrelated to pituitary gland height (7).…”
mentioning
confidence: 99%